Penggunaan QRIS Untuk Kemudahan Pembayaran Digital Dari Perspektif Kepuasan Konsumen - Fitri Raudah Rahmah; Nur Rahayu Sabrina Damayanti; Rafly Armazumi; Zul Azmi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
The aim of this research is to find out whether consumer satisfaction with the use of QRIS is satisfactory or not. The use of payment instruments has progressed very significantly. This change is in the form of a digital payment tool which is very helpful and speeds up the payment process and helps reduce physical contact as a form of reducing the spread of the Covid-19 virus which can be attached to banknotes as a means of payment. QRIS is the Indonesian Quick Response Code Standard which is the National QR code standard as a QR code payment medium in Indonesia which was launched by Bank Indonesia. Using one E-Wallet as a means of payment for several merchants such as Link Aja, Gopay, OVO, DANA, ShopeePay and others. The data obtained came from a questionnaire link which contained several statements regarding consumer satisfaction with the use of QRIS for digital payments which researchers had distributed via social media. And the analysis technique used is based on a quantitative approach. Data collection was carried out through interviews, observation and distributing questionnaires.